FEATURES OF THE INTRODUCTION OF WATER-SAVING TECHNOLOGIES IN THE REPUBLIC OF UZBEKISTAN - Jalolov Sherzod Rustamovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the theoretical and practical issues of the introduction of water-saving technologies in the Republic of Uzbekistan, types of water-saving technologies, the organizational and legal basis for the effective use of water resources, the necessary measures for the careful use and management of water resources.